Studies on the Preparation and Composition of Guava (Psidiuni guajava L.) Toffee and Slab Bars - Alizai, Mohammad Nisar Khan (Biological Sciences - PJSIR, 2007)
uava toffee/sl ab bars were made from gu ava pul p u si n g hot a i r deh yd ra tion . No arti ficial colou r, preservati ve or e sence wa s added to th e prod uct. Com parative i n vc ·ti gation of the fresh guava pul p an d th e product was cond u cted . Moi ·t u re, ash , sol ubl e pecti n , ascorbi c a id , tann i n s, sugar, ci tr i c aci d a l on g with m ineral contents i .e. ca l ci um , sodium , potassi u m an d ph o ph ru s we re determ i n ed . h e!f l i fe of the prod uct w as mon i tored for more th an twel ve month s an d orga11ol eptic eva l u a ti on wa s cond ucted. No chan ge i n col ou r, n avou r or tex tu re wu s observed during t h e storage a t room tem perat ure.